(untitled) (Global Journals of Research in Engineering, 2025)
The R-Verdict Schema a UI design model based on the principles of Relevance and Relation of UI elements and components to interaction concepts has gained recognition for its simple and decisive approach to interface design While its theoretical framework has been well received its practical use impact on designers remains unexplored This study investigates how a team of novice designers apply the R-Verdict Schema in real design tasks evaluating its effectiveness in enhancing usability consistency and decision-making Through controlled experiments and qualitative feedback we assess how the model aids novice designers in structuring interfaces improving element relationships and fostering intuitive interactions The findings reveal that the schema significantly supports beginners in developing cohesive UI layouts and making design choices that align with user expectations This research contributes to UI UX education by demonstrating the schema s potential as a guiding framework for early-stage designers ultimately reinforcing the value of structured design methodologies in digital interface development